Imaging the interaction between dengue 2 virus and human blood platelets using atomic force and electron microscopy - Ghosh, Kanjaksha; Gangodkar, Shobha; Jain, Preksha; Shetty, Shrimati; Ramjee, Sandhya; Poddar, Pankaj; Basu, Atanu (Journal of Electron Microscopy, 2008)
Thrombocytopenia is frequently associated with dengue virus infection. Host factors such as anti-platelet immunopathogenic processes have been implicated in the origin of dengue-associated thrombocytopenia but the role of dengue virus in directly interacting with platelets and altering their hemostatic property remains incompletely understood. In the present study, we examined the effect of dengue 2 virus on the morphology and physiological activation profile of normal human platelets using atomic force microscopy, electron microscopy and flowcytometry. Platelets obtained from healthy donors were exposed to a cell culture-adapted 10(4) LD(50) dengue 2 virus isolate in vitro and the subsequent effect on morphology and activation biology studied. Our results show that dengue 2 virus exposure at doses comparable to natural viremic states in human infections can activate platelets with an increase in P-selectin expression and fibrinogen-binding property. Atomic force, scanning and transmission electron microscopy also showed typical activation-related morphological changes such as altered platelet membrane architecture, degranulation, presence of filopodia and dilatation of the open canalicular system in the dengue 2 virus-exposed platelets but not in the controls. Importantly, Japanese encephalitis virus exposure at the same dose did not activate platelets or show any morphological changes. Our findings suggest that dengue 2 virus may directly interact with and activate platelets - an event that might be important in the origin of dengue-associated thrombocytopenia. Detailed molecular characterization of this effect might provide key knowledge toward better prophylaxis of the hemostatic complications of dengue disease.
Keywords: AFM; dengue virus; Electron microscopy; platelet

Synthesis of novel rhodamine type anthrone Spiro-lactam (ASL) analogues and evaluation of antiviral activity against dengue and chikungunya viruses - Darole, Ratanamala S.; Bagad, Pooja K.; Gonnade, Rajesh G.; Alagarasu, Kalichamy; Punekar, Madhura; Shukla, Shridhar; Parashar, Deepti; Senthilkumar, Beeran (European Journal of Medicinal Chemistry, 2023)
A series of Rhodamine type Anthrone-Spirolactam (ASL) derivatives Benzylimin-Anthrone-Spirolactam (ASL-1 to ASL-10) and Benzamide-Anthrone-Spirolactam (ASL-11 and ASL-12) were synthesized via a simple condensation reaction between Anthrone Spiro-lactamine (2) and various aromatic aldehyde and acyl chlorides respectively. Since rhodamine-based compounds were reported to have antiviral activity, the ASL derivatives were examined for in vitro antiviral activity against dengue and chikungunya viruses. Among all the analogues, ASL-3, ASL-6, ASL-7, ASL-8, ASL-9 and ASL-10 were the most potent against dengue virus (DENV) and exerted around one log reduction in virus titre under post -treatment conditions. At the same time ASL-3 was effective under cotreatment conditions. Two analogues ASL-6 and ASL-12 exerted anti-chikungunya virus (CHIKV) activity under post -treatment conditions. In silico docking studies revealed that the ASL derivatives interacted with the proteins of DENV and CHIKV. Together, the results suggest the anti-DENV and CHIKV activity of ASL derivatives which may be exploited further for therapeutic purposes.
Keywords: Anthrone Spiro-lactam; Chikungunya virus; dengue virus; Rhodamine